Improving Students’ Reading Comprehension Achievement Through Wattpad Media Of Eleventh Grade At SMA Swasta Bandung - Septiani Fadillah, Teguh Satria Amin (Pusdikra Publishing, 2022)
This study aims to improve students' reading comprehension through Wattpad media. This study analyzes how the use of Wattpad media can improve students' reading comprehension achievement. This research was conducted in SMA Swasta Bandung. The subjects of this study were students of class XI, totaling 30 students. This research uses Classroom Action Research (CAR). There are two cycles to give students more opportunities to improve their understanding of how to find the main idea and understand the message well and effectively. The results showed that the students' reading ability increased significantly. In the pretest the average score was 29.83, in the first cycle the average score was 44.67, and in the second cycle, the average score was 79.67. The increase was also seen from the percentage of students who passed the KKM in reading narrative texts, in the pre-test, 6.67% of students got more than 75 points, in cycle 1 16.67% students got more than 75 points, and in cycle 2 70% students got more than 75 points. So, this media can help students to remember the main information and ideas from the texts they read, students can also enrich their vocabulary. Based on the results of this study, the researcher recommends the use of Wattpad media in reading because Wattpad can improve reading comprehension achievement